Numerical Design of CoNi-Base Superalloys With Improved Casting Structure - Wahlmann, Benjamin; Bandorf, Jakob; Volz, Nicklas; Förner, Andreas; Pröbstle, Johannes; Multerer, Kerstin; Göken, Mathias; Markl, Matthias; Neumeier, Steffen; Körner, Carolin (Metallurgical and Materials Transactions A-Physical Metallurgy and Materials Science, 2022)
Numerical methods can accelerate the design of alloys with improved material properties. One approach is the coupling of multi-criteria optimization with CALPHAD-based models of alloy properties. While this technique has already yielded promising new Nickel-base superalloys, the applicability to CoNi-base alloys has not yet been investigated. These alloys show promising properties for application as wrought high-temperature materials. We designed three CoNi-base superalloys, which were optimized for either high strength or high chemical homogeneity. The alloys were cast, and mechanical and thermophysical properties were characterized. The alloy optimized for strength showed creep performance inferior to a conventionally designed CoNi-alloy but had a much lower density. For developing highly homogeneous alloys, Scheil calculations were implemented in the optimization routine to quantify the severity of segregation. Non-equilibrium phases could be predicted successfully, resulting in a degree of homogeneity that rivaled that of a low-segregation ternary Co-base alloy. A comparison of elemental partitioning behavior and phase transition temperatures with CALPHAD calculations showed that trends are well represented for the most part. Finally, the applicability of the alloy design approach for Co-rich superalloys is evaluated, and possible applications for the optimized alloys are discussed.
CRIS-Team WoS Importer:2022-12-02